The mineral resources of Newfoundland [electronic resource] - Howley, James P., 1847-1918. ([St. John's, Nfld.? : s.n.], 1909)
Errata slip inserted at p. [1] Cover title. Electronic reproduction. Mode of access: Internet. 44